EFFECT OF DNA CONSTRUCTIONS ELECTROPORATION ON DENDRITIC CELLS - A. S. Bulygin; V. P. Tereshchenko; R. Yu. Zavodskii; I. A. Obleukhova; S. V. Sennikov; A. N. Silkov (Медицинская иммунология, 2021)
Today transfection of mammalian cell with DNA or RNA construction is the only method for delivering programmed information into the cell nucleus. Electroporation is most commonly used method of transfection in experiments with dendritic cell. The aim of electroporation is to permeabilize the membrane by passing electric impulse through the cell. Due to the increase permeability of the membrane chance DNA or RNA construction getting inside into the cell is increased, wherein survival of the cells is decreased.In the study male mice C57Bl/6 line 2-4 months old were used. From femur bones was isolated 20 × 106 bone marrow cells, which were cultured in 20 mL of complete RPMI-1640 for 7 days. To generate dendritic cells from BM cells, 100 ng/mL of rmFlt3-L was added to culture media at day 0. After 7 days of cultivation, the cell cultures were electroporated with control noncoding plasmids p5 (EP P5) or pmaxCCR9 encoding mouse chemokine receptor CCR9 (EP CCR9). The controls were cell cultures electroporated without any plasmids (mock EP) and cell cultures without electroporation (none EP). 5 × 105 cells were electroporated and resting for 10 minutes. After 10 minutes, cells were harvested and seeded into 24-well plates in 1 mL of culture medium and conditioning medium (1:1). Then, 50 ng/mL of Flt3-L was added to each well. The next day, transfected cells were collected and used for flow cytometry, qRT-PCR analysis.It was found that after electroporation in the groups mock EP, EP P5, EP CCR9 relative amount of live CD11c+ dendritic cells was significantly less than in the non EP group. Moreover, in the EP P5 and EP CCR9 groups the frequency of live CD11c+ dendritic cells was significantly less than in the mock EP group. Expression of the CD86 marker in the EP P5 and EP CCR9 groups was significantly higher than in the non EP and mock EP groups. Expression of the I-AB(MHCII) in the EP CCR9 group on cDC2s was significantly higher than in the non EP group. On plasmacytoid DCs (pDCs) and conventional type 2 DCs (cDC2s) in the EP CCR9 group expression of CCR9 was significantly higher than in the non EP group. Therefore, in this study, we demonstrated the effectiveness of electroporation, accompanied by the decrease in the survival rate and maturation of DCs.